Brain Tumor Detection Method Using Unsupervised Classification Technique - Mahdi, A. S.; Essa, S.O. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Magnetic  Resonance  Imaging  (MRI)  is  one  of  the  most important diagnostic tool. There are many methods to segment thetumor of human brain. One of these, the conventional method that uses pure image processing techniques that are not preferred because they need human interaction for accurate segmentation. But unsupervised methods do not require any human interference and can segment   the   brain   with   high   precision.   In   this   project,   the unsupervised  classification methods have been used in order to detect the tumor  disease from MRI images.    These methods involved KÂ mean or Isodat, which were based on the digital value distribution. The results show the classification process was a powerful tool to identify the Tumor disease from MRI images.   All results were evaluated  by  using the ENVI Version 3.2 facility.